2020
DOI: 10.1186/s13148-020-00905-6
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic measures of ageing predict the prevalence and incidence of leading causes of death and disease burden

Abstract: Background: Individuals of the same chronological age display different rates of biological ageing. A number of measures of biological age have been proposed which harness age-related changes in DNA methylation profiles. These measures include five 'epigenetic clocks' which provide an index of how much an individual's biological age differs from their chronological age at the time of measurement. The five clocks encompass methylation-based predictors of chronological age (HorvathAge, HannumAge), all-cause mort… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
124
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(135 citation statements)
references
References 54 publications
8
124
3
Order By: Relevance
“…Our findings are in line with the literature in cohorts of European ancestry, showing that GrimAA outperforms other measures in its association with CVD incidence [ 21 , 22 ]. The effect size of GrimAA on CVD incidence appears to be remarkably similar across studies in European ancestry, and similar to our estimate in African Americans.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our findings are in line with the literature in cohorts of European ancestry, showing that GrimAA outperforms other measures in its association with CVD incidence [ 21 , 22 ]. The effect size of GrimAA on CVD incidence appears to be remarkably similar across studies in European ancestry, and similar to our estimate in African Americans.…”
Section: Discussionsupporting
confidence: 92%
“…The effect size of GrimAA on CVD incidence appears to be remarkably similar across studies in European ancestry, and similar to our estimate in African Americans. Comparing the same four measures of epigenetic acceleration that we investigated, Hillary et al found that over thirteen years of follow-up, GrimAA outperforms the other measures in terms of its association with incidence of heart disease (HR: 1.41, 95% CI 1.18–1.68, per 1 SD) [ 21 ]. Wang et al found that a 1 SD increase in GrimAA was associated with elevated risk of myocardial infarction (HR: 1.44, 95% CI 1.16–1.79) and stroke (HR: 1.42, 95% CI 1.06–1.91) in a study of elderly participants from the Normative Ageing Study and the Cooperative Health Research in the Region of Augsburg (KORA) study [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that Horvath’s and Hannum’s algorithms are statistically significantly associated with all-cause mortality in older general populations [ 20 23 ]. Consistent with our findings, DNAmMRsocre, PhenoAge and GrimAge outperformed the first generation of DNAm aging algorithms regarding mortality prediction [ 8 , 9 , 24 26 ]. Few studies have focused on the prognostic values of DNAm aging algorithms among cancer patients.…”
Section: Discussionsupporting
confidence: 90%